2022
DOI: 10.1002/jssc.202100663
|View full text |Cite
|
Sign up to set email alerts
|

Development of a method to screen and isolate xanthine oxidase inhibitors from black bean in a single step: Hyphenation of semipreparative liquid chromatography and stepwise flow rate countercurrent chromatography

Abstract: Development of a method to screen and isolate xanthine oxidase inhibitors from black bean in a single step: hyphenation of semipreparative liquid chromatography and stepwise flow rate countercurrent chromatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…It also relieved the swelling of the ankle joints and decreased inflammatory cell infiltration around the ankle joints. These studies indicate that this plant has the potential to reduce hyperuricemia (Zhang et al 2022).…”
Section: Moroccon Medicinal Plantsmentioning
confidence: 89%
See 2 more Smart Citations
“…It also relieved the swelling of the ankle joints and decreased inflammatory cell infiltration around the ankle joints. These studies indicate that this plant has the potential to reduce hyperuricemia (Zhang et al 2022).…”
Section: Moroccon Medicinal Plantsmentioning
confidence: 89%
“…The aqueous extract of Dendrobium candidum leaves (DLE) could decrease the level of uric acid in rats was found through a study. The therapeutic efficacy of the Dendrobium candidum leaf extract on hyperuricemia was investigated (Zhang et al 2022). The results indicated that biochemical parameters of kidney and liver function, specifically uric acid levels in serum, were ameliorated with DLE, which may be related to a reduction of XO and adenosine deaminase (ADA) in the liver.…”
Section: Dendrobium Candidummentioning
confidence: 99%
See 1 more Smart Citation
“…It accounted for 15.81% of the constituents in an extract of Puerariae flos and was the component of the extract with the greatest ability to inhibit XO (the other components are tectoridin, ononin, and biochanin A) (Liu et al., 2017). Genistein and daidzein are the main active substances in soybean okara, black bean and P. lobata roots, and potential functional ingredients that may act as natural therapeutic agents for conditions involving XO (Nile et al., 2020; Niu et al., 2022; Tang et al., 2020).…”
Section: Mechanism Of Xo Activity and Hua Inhibition By Flavonoidsmentioning
confidence: 99%